Alterations in serum levels of trace element in patients with breast cancer before and after chemotherapy - norjis ahmadi; Soleiman Mahjoub; Reza Hajihosseini; Mostafa Taherkhani; Dariush Moslemi (Babol University of Medical Sciences, 2018)
Background: Breast cancer is the most common serious disease around the world. The trace elements have a vital role in the metabolism and chemotherapy may change the level of metal ions. Due to the ambiguity of the existence in this regard, the study examined the trace element serum levels in women with breast cancer before and after chemotherapy . Methods: Sixty patients were studied undergoing specialist. First sampling was taken before chemotherapy (after 4 weeks of surgery) and second sampling was taken after the completion of 3 courses of chemotherapy, approximately 9 weeks after the first chemotherapy. The patients took Adriamycin 60mg/m2 Cytoxan 600mg/m2. Serum zinc and iron levels were measured using standard spectrophotometric method. Measurement of serum copper was done by atomic absorption spectroscopy. Results: Serum zinc and iron levels in women after chemotherapy significantly decreased (p<0.001), however, the serum level of copper increased but was not significant (P=0.676). Conclusions: Our findings demonstrate significant decrease in zinc and iron levels in breast cancer patients after 3 courses of Adriamycin and Cytoxan chemotherapy. Prescribing zinc supplements can be useful after chemotherapy